2021
DOI: 10.1111/bcp.15126
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of fluvoxamine in COVID‐19 ICU patients: An open label, prospective cohort trial with matched controls

Abstract: Aims Fluvoxamine, a selective serotonin reuptake inhibitor (SSRI) and sigma‐1 receptor agonist, has so far shown promise in the prevention of COVID‐19 progression as an early treatment option in three trials. The aim of this study was to evaluate the safety and efficacy of fluvoxamine in COVID‐19 patients if administered later in the course of the disease. Methods The study was designed as an open‐label, prospective cohort trial with matched controls. In April and May 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(94 citation statements)
references
References 38 publications
(61 reference statements)
3
82
0
Order By: Relevance
“…A limitation of our study is that our patient population did not have any patients taking fluvoxamine and this is in direct contrast to the French study and to an open label, prospective cohort study of fluvoxamine in ICU patients with COVID-19 from Croatia [ 8 , 40 ]. In the Croatian group, 51 COVID-19 patients with severe disease admitted to the ICU were started on fluvoxamine 100 mg three times per day for 15 days in addition to standard therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of our study is that our patient population did not have any patients taking fluvoxamine and this is in direct contrast to the French study and to an open label, prospective cohort study of fluvoxamine in ICU patients with COVID-19 from Croatia [ 8 , 40 ]. In the Croatian group, 51 COVID-19 patients with severe disease admitted to the ICU were started on fluvoxamine 100 mg three times per day for 15 days in addition to standard therapy.…”
Section: Discussionmentioning
confidence: 99%
“…7 Another clinical open-label trial with fluvoxamine in n = 51 intensive care unit-treated patients showed a 42% reduction in mortality compared with matched controls. 8…”
Section: Impact On Disease Coursementioning
confidence: 99%
“…Of the 155 abstracts, a total of 96 abstracts was excluded due to the reasons mentioned in the PRISMA flow diagram ( Figure 01 ). Consequently, full texts of 11 studies were assessed for eligibility of which 8 were excluded (7 studies did not meet the first eligibility criteria and 1 study was reported among patients admitted to the ICU [21] . Additionally, no studies were identified through hand-searching of the reference list of the included studies.…”
Section: Resultsmentioning
confidence: 99%